Renewable Energy for Overcoming the Dilemma of Darkness in Nigerian Urban Centers - Sanusi, Yeken A. (CSID Journal of Infrastructure Development, 2022)
Cities are unique centers of energy demand and greenhouse gas emissions. Although electricity provides multiple functions for urban residents, its supply in Nigerian urban centers is poor, and the attempts to understand this problem have been limited to national level. Therefore, this study aims to explore the dimensions of electricity supply problem; assess adaptations by households to inadequate electricity supply; examine the use of renewable energy-related facilities; and understand the perception of renewables by urban households, with five residential neighborhoods in Minna, the capital of Niger state, were covered. Data were collected using a questionnaire and the Facility Observatory Technique to document daily electricity supply to households. The collected data covered electricity connection, daily supply, adaptations to inadequate public supply, perception of renewable energy and willingness to shift to renewable electricity sources. Results indicate that households in Minna have an average of 5 hours of electricity daily, while only 25% have electricity at night (7.00pm and 10.00pm.). An index derived to demonstrate the nature of electricity supply to households indicates that the city has a darkness index of 0.81, indicating a situation of extreme inadequacy of electricity supply. The index has a 95% correlation with the proportion of households without electricity at night. The study also shows that 72% of the households use fossil fuel-driven plants while 84% are not familiar with the use of renewable resources for generating electricity. The paper holds that the willingness of the public to switch to renewable energy, the incremental nature of urban development, and the high costs incurred by households for non-sustainable alternative sources of electricity provide the foundation for a more concerted effort to develop renewable energy as a means of improving the availability of electricity in Nigerian urban centers.